2015
DOI: 10.1007/s00775-015-1266-2
|View full text |Cite
|
Sign up to set email alerts
|

Participatory role of zinc in structural and functional characterization of bioremediase: a unique thermostable microbial silica leaching protein

Abstract: A unique protein, bioremediase (UniProt Knowledgebase Accession No.: P86277), isolated from a hot spring bacterium BKH1 (GenBank Accession No.: FJ177512), has shown to exhibit silica leaching activity when incorporated to prepare bio-concrete material. Matrix-assisted laser desorption ionization mass spectrometry analysis suggests that bioremediase is 78% homologous to bovine carbonic anhydrase II though it does not exhibit carbonic anhydrase-like activity. Bioinformatics study is performed for understanding t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…The results suggested that SiO 2 -NPs assembled to from silica ball due to the interaction of bioremediase protein and TEOS solution. It similarly confirmed the successful synthesis of Si-NPs using bioremediase protein from TEOS as an organic precursor [14]. The synthesized Si-NPs were quite regular in shape and consistently dispersed as observed in both FE-SEM and TEM images.…”
Section: Morphological and Compositional Characterization Of Sio 2 -Npssupporting
confidence: 77%
See 1 more Smart Citation
“…The results suggested that SiO 2 -NPs assembled to from silica ball due to the interaction of bioremediase protein and TEOS solution. It similarly confirmed the successful synthesis of Si-NPs using bioremediase protein from TEOS as an organic precursor [14]. The synthesized Si-NPs were quite regular in shape and consistently dispersed as observed in both FE-SEM and TEM images.…”
Section: Morphological and Compositional Characterization Of Sio 2 -Npssupporting
confidence: 77%
“…The possible vibrational bands shown at 1097 cm -1 (ν as : Si-O) and 790 cm -1 (ν s : Si-O) were the two strong evidence of the formation of SiO 2 -NPs. The absorption bands appeared between 800 and 1269 cm -1 had been ascribed as a superimposition of assorted SiO 2 peaks, Si-OH bonding and residual organic groups [14]. The amorphous nature of prepared SiO 2 -NPs was confirmed from the XRD observation (Fig.…”
Section: Ftir and Xrd Analysismentioning
confidence: 76%
“…In thermolysin from Bacillus thermoproteolyticus , a metalloprotease, a Zn 2+ ion plays a catalytic but not a structural role, and it does not contribute to the unusually high thermal stability of the enzyme [ 52 ]. However, a structural and functional role for Zn 2+ is known for other thermostable enzymes, namely bioremediase [ 53 ]. All Ts2631 endolysin substitution variants were soluble at 60°C, which is the temperature that the lytic activity tests were performed ( Fig 6B ).…”
Section: Resultsmentioning
confidence: 99%
“…This has led to the isolation and identification of a number of metal-reducing bacteria. Three bacterial strains so isolated and partially characterized from water of the 65 °C hot spring consortium were found efficacious for enhancement of concrete strength, silica leaching activity and other industrial applications [7], [8], [9], [10], [11], [12].…”
Section: Introductionmentioning
confidence: 99%